Analysis of Accounting Information Systems on MSME Performance with Emotional Intelligence as Moderation - Ekamarinda, Een Yulaika; Heny, Heny; Rizal, Noviansyah (Assets : Jurnal Ilmiah Ilmu Akuntansi, Keuangan dan Pajak, 2024)
Good Emotional Intelligence (comprising self-awareness, motivation, and social skills) enables one to make appropriate decisions under a variety of circumstances. An organization's accounting information system is a device utilized to streamline the majority of business operations, regardless of the company's size (small, medium, or large). Due to the fact that MSMEs are a primary driver of economic expansion, the creation of new employment is crucial to their ability to make sound decisions.The analysis technique refers to a process of data analysis designed to yield information that can be utilized in this study. In order to facilitate researchers' comprehension of the data as a foundation for decision making, it is necessary to analyze the data for interpretation. The present study employed the Partial Least Squares (PLS) methodology is carried out in in three stages: Outer model analysis, Inner model analysis, Hypothesis testing. In accordance with the formal model, latent variables are defined explicitly as linear aggregates of observed variables or their indicators. In order to generate weight estimates for latent variable score components, the inner and outer model specifications are compared.Determine the impact of emotional intelligence (self-awareness, motivation, and social skills) on the performance of micro, small, and medium-sized enterprises (MSME) in relation to the implementation of accounting information systems. The primary data utilized in this study were collected through the distribution of questionnaires to MSME entrepreneurs in Jember Regency, who provided their responses. Clearly, the accounting information system plays a crucial role in the progress and growth of MSMEs. Emotional Intelligence has no appreciable impact on the efficacy of MSME businesses as it relates to accounting information systems. Nonetheless, Emotional Intelligence significantly impacts the business performance of SMEs.